Investigating the Effect of Oil Palm Fiber as Filler Material in HMA Mix Design - Chan, Ron Aldrino; Ron, Buking; Chai, Sin Lei (ENCON 2013, 2013)
A study was carried out on the hot mix asphalt (HMA) mixtures by using the raw oil palm fiber as filler material with gradation limit of ACW 14 for heavy traffic volume road. These fibers were cut into approximately 1cm in length and the percentages of raw oil palm fiber used as filler in HMA mixtures were proposed to be 0.1%, 0.2% and 0.3% respectively. The objectives of this study were to evaluate the effect of oil palm fiber as filler material in the modified Marshall Mix Design as a comparison with conventional mix. The results showed that with the addition of the raw oil palm fiber contents the stability decreases while the flow values increase as well as the air voids in the HMA samples. However, all the test samples for the modified HMA samples were unable to meet the JKR requirements except for the flow results. In addition, three of the Marshall mix properties (Voids in Total Mix (VTM), Voids in Mineral Aggregate (VMA) and Voids Filled with asphalt (VFB)) were found to be more sensitive to the changes of percentage of raw oil palm fibers. Accordingly, from the results there was an increased trend in voids content in the modified mixtures. Therefore, this indicates that raw oil palm fibers used in this study are not suitable in reducing air voids content in HMA mixtures.